Unraveling the Life Problems of the Samin Kudus Community with Indigenous Counseling - Farikhatul 'Ubudiyah; Rosi Sabiqotul Chasna; Ahmad Yunus (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
The Samin Kudus community is a minority group in where they reside which creates a conflict of citizenship rights. In addition, they have values that are maintained amidst the multicultural onslaught. This article aims to find out how indigenous people who adhere to Sedulur Samin in the vsniillages of Larikrejo and Karangrowo, Undaan sub-district, Kudus district, solve problems in indigenous counseling studies. The theory used is about indigenous psychology which studies the unique behavior of indigenous people. This study used a qualitative-exploratory method which was conducted in the villages of Larikrejo and Karangrowo, Kudus Regency in 2022. Data were collected through observation, interviews, and documentation. Data analysis was carried out by reducing data, presenting data, and verifying. Data validity was carried out using triangulation of data collection methods. The results of the study describe the concept of indigenous counseling in the Samin Kudus community, there are: (a) botoh plays a role in guiding Sedulur Sikep who can be called a non-professional counselor; (b) the principle of counseling in the form of equality of understanding between botoh and sedulur; (c) components of counseling relationships based on the principles of ancestral teachings; and (d) there are stages of values taught by botoh to Sedulur Sikep. With the indigenous counseling process, indigenous peoples can solve life problems related to the physical, psychological, social and spiritual according to the values they believe in.